Mare Clausum: The Formation of the Law of the Sea in Pre-modern State Practice and Legal Doctrine (c. 1350-1650) - Cattelan, Stefano (Human Rights and Humanitarian Law E-Books Online, Collection 2026., 2025)
Who owns the sea? This book explores this timeless question by tracing the development of claims over the sea from the late Middle Ages to the early modern era, shedding light on the complex interplay between legal arguments, political interests, and geostrategic realities. By the time Hugo Grotius's Mare liberum (1609) famously championed the freedom of the seas, competing traditions of 'claimed seas' had already shaped European legal debates for centuries. Examining three macro-regions - the Mediterranean, the seas of Northern Europe, and the world oceans - this study challenges the dominant Grotius-centric narrative, offering a broader perspective on how political actors and jurists justified exclusive maritime rights long before John Selden's Mare clausum (1635). While assessing the Eurocentric foundations of the modern law of the sea, it reveals how historical legal arguments and notions continue to shape contemporary ocean governance.